Lettere dalla Spagna Sugli epistolari a Oreste Macrí - Trentini, Nives (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2004)
The book offers a summary of over 1,400 letters on Hispanic matters written by Hispanic senders to Oreste Macrí over the course of fifty years (1950-1998). The salient events of Macrí's intellectual life (editorial assignments, conferences, translations) and the proximity of his correspondents to the hermetic environment emerge. Alongside Macrí, significant personalities of poets and critics are presented (Aurora de Albornoz, Joaquín Arce, Pablo Luis Ávila, Américo Castro, Rafael Lapesa, Fernando Lázaro Carreter, Francisco López Estrada, Alonso Zamora Vicente). The letters of Ramón Menéndez Pidal, Américo Castro, Isabel and Francisco García Lorca are collected and annotated in an Appendix.